Realization of Economic Green-Crop-House to Improve Horticulture Diversity - Heri Ardiansyah; Rohmatin Agustina; Suhaili Suhaili (OJS Universitas Muhammadiyah Gresik, 2020)
Supplementary foods beside of rice that meet the body's nutrition, among others, can be sourced from vegetables and fruit. The sustainable food house movement initiated by the government through the main women-community program has greatly helped to reduce the impact of this problem. Sustainable food house is a movement to grow vegetables and fruit in the yard of the house as an effort to fulfill the people's nutrition which can be consumed economically without having to buy but through the movement to plant and harvest fruits and vegetables. Fulfillment of plant seeds as a source of material for this movement is one of the limiting factors for the success of this program. The activity of women community that we do is making the